Global Update: Canada. (November 2012) - Willemse, Lisa; Ogbogu, Ubaka; Johnson, Stacey; Rudnicki, Michael
If Canadians have a global reputation for being 'nice', then our propensity for scientists to collaborate should come as no surprise. The Canadian stem cell and regenerative medicine field is particularly strong in terms of collaboration, research results and innovative programs to leverage investments in the sector. Canada continues to see significant achievements and changes that will have a broad impact on the ability to move translational research forward in the near future.